Inactivation of the mouse sperm receptor, mZP3, by site-directed mutagenesis of individual serine residues located at the combining site for sperm - Chen, Jie (The National Academy of Sciences, 1998)
To initiate fertilization, mouse sperm bind to Ser- (O-) linked oligosaccharides located at the sperm combining site of zona pellucida glycoprotein mZP3. Apparently, the oligosaccharides are present on one or more of five Ser residues clustered in the carboxyl-terminal region of the mZP3 polypeptide. Here, each of the Ser residues, as well as an intervening Asn residue, was converted to a small, nonhydroxy amino acid by site-directed mutagenesis. Mouse embryonal carcinoma (EC) cells were then stably transfected with the wild-type and mutated mZP3 genes. In each case, transfected cells synthesized and secreted recombinant EC-mZP3 into the culture medium. The glycoproteins were partially purified and assayed for their ability to inhibit binding of sperm to ovulated eggs in vitro. As compared with wild-type EC-mZP3, mutations of Ser-329, Ser-331, or Ser-333 had no effect on sperm receptor activity. Mutation of Asn-330, a potential N-linked glycosylation site, also had no effect on sperm receptor activity. On the other hand, mutation of either Ser-332 or Ser-334, or mutation of Ser-332, Ser-333, and Ser-334, resulted in complete inactivation of EC-mZP3 as a sperm receptor. These results suggest that Ser-332 and Ser-334, residues conserved in mouse, hamster, and human ZP3, are essential for sperm receptor activity.